2013
DOI: 10.1111/ijn.12148
|View full text |Cite
|
Sign up to set email alerts
|

Non‐family support for breastfeeding maintenance among career women in Taiwan: A qualitative study

Abstract: The purpose of the study was to describe the influence of non-family-based support on breastfeeding practices among career women in Taiwan during the first four postnatal months. A qualitative, case study approach was used to investigate the phenomenon. A purposive sample of 14 women was recruited and took part in two to three in-depth interviews. The data were transcribed and analysed using descriptive content analysis. It was found that non-family supports had significant influence on their efforts to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(108 reference statements)
0
4
0
3
Order By: Relevance
“…Mothers expected that society members could provide emotional support. Participants in other studies also agreed that a supportive community was very important for breast-feeding (17,26,27) . Previous studies showed that some society members had a negative response to breast-feeding in public places.…”
Section: Discussionmentioning
confidence: 95%
“…Mothers expected that society members could provide emotional support. Participants in other studies also agreed that a supportive community was very important for breast-feeding (17,26,27) . Previous studies showed that some society members had a negative response to breast-feeding in public places.…”
Section: Discussionmentioning
confidence: 95%
“…Women are more likely to maintain breastfeeding when they are aware of breastfeeding support policies for their companies. 32 However, none of the managers in this study re-ported having anything written about breastfeeding. Such policy significantly increases the chance of the worker to continue to breastfeed.…”
Section: Discussionmentioning
confidence: 88%
“…A assistência dos profissionais de saúde foi relacionada com a melhoria da amamentação na Indonésia (9) . Em Taiwan, permanecer em centro de cuidados no primeiro mês pós-parto influenciou positivamente na prática, devido apoio e aconselhamento de profissionais, especialmente enfermeiros (10) . E mães de Hong Kong, retornam ao trabalho e recebem educação profissional adicional (11) .…”
Section: Categoria 1: Tipos De Apoio Durante a Manutenção Da Amamentaçãounclassified
“…Porém, nem todas as mulheres retornam ao trabalho devido à falta de apoio (10,(12)(13) . Alguns empregadores têm atitudes positivas em relação ao provi- A prática do aleitamento materno entre as trabalhadoras formais: revisão integrativa de literatura mento de um ambiente favorável à mãe no trabalho.…”
Section: Categoria 1: Tipos De Apoio Durante a Manutenção Da Amamentaçãounclassified
See 1 more Smart Citation